Cybersecurity - Attack and Defense Strategies - Second Edition - Diogenes, Yuri; Ozkaya, Erdal (Packt Publishing, 2019)
Updated and revised edition of the bestselling guide to developing defense strategies against the latest threats to cybersecurity Key Features Covers the latest security threats and defense strategies for 2020 Introduces techniques and skillsets required to conduct threat hunting and deal with a system breach Provides new information on Cloud Security Posture Management, Microsoft Azure Threat Protection, Zero Trust Network strategies, Nation State attacks, the use of Azure Sentinel as a cloud-based SIEM for logging and investigation, and much more Book Description Cybersecurity - Attack and Defense Strategies, Second Edition is a completely revised new edition of the bestselling book, covering the very latest security threats and defense mechanisms including a detailed overview of Cloud Security Posture Management (CSPM) and an assessment of the current threat landscape, with additional focus on new IoT threats and cryptomining. Cybersecurity starts with the basics that organizations need to know to maintain a secure posture against outside threat and design a robust cybersecurity program. It takes you into the mindset of a Threat Actor to help you better understand the motivation and the steps of performing an actual attack - the Cybersecurity kill chain. You will gain hands-on experience in implementing cybersecurity using new techniques in reconnaissance and chasing a user's identity that will enable you to discover how a system is compromised, and identify and then exploit the vulnerabilities in your own system. This book also focuses on defense strategies to enhance the security of a system. You will also discover in-depth tools, including Azure Sentinel, to ensure there are security controls in each network layer, and how to carry out the recovery process of a compromised system. What you will learn The importance of having a solid foundation for your security posture Use cyber security kill chain to understand the attack strategy Boost your organization's cyber resilience by improving your security policies, hardening your network, implementing active sensors, and leveraging threat intelligence Utilize the latest defense tools, including Azure Sentinel and Zero Trust Network strategy Identify different types of cyberattacks, such as SQL injection, malware and social engineering threats such as phishing emails Perform an incident investigation using Azure Security Center and Azure Sentinel Get an in-depth understanding of the disaster r ...